2020
DOI: 10.1002/emp2.12258
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of end‐of‐life care in an emergency department–based intensive care unit

Abstract: Funding and Support: By JACEP Open policy, all authors are required to disclose any and all commercial, financial, and other relationships in any way related to the subject of this article as per ICMJE conflict of interest guidelines (see www.icmje.org). The authors have stated that no such relationships exist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(29 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…Fifteen studies emerged from the United States [29][30][31][32][33]35,[39][40][41][42][43][44][45][46]50 ; two each from France 38,48 and Singapore 28,36 ; and one each from Finland, 34 Ireland, 47 Canada, 37 and Taiwan. 49 The study designs employed by the included studies were retrospective (n = 11), 28,29,34,[38][39][40][41][42][43]46,50 prospective cohort (n = 5), 31,33,36,37,48 randomized controlled trial (n = 2), 22,32 quasi-experimental (n = 2), 47,49 pilot (n = 1), 44 and crosssectional (n = 1). 45 One study employed a program development approach with no outcomes assessed.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Fifteen studies emerged from the United States [29][30][31][32][33]35,[39][40][41][42][43][44][45][46]50 ; two each from France 38,48 and Singapore 28,36 ; and one each from Finland, 34 Ireland, 47 Canada, 37 and Taiwan. 49 The study designs employed by the included studies were retrospective (n = 11), 28,29,34,[38][39][40][41][42][43]46,50 prospective cohort (n = 5), 31,33,36,37,48 randomized controlled trial (n = 2), 22,32 quasi-experimental (n = 2), 47,49 pilot (n = 1), 44 and crosssectional (n = 1). 45 One study employed a program development approach with no outcomes assessed.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Multiple recent studies have demonstrated benefits of ED‐ICUs, including observed reduction in mortality, reduction in rates of ICU admission or hospitalization, and reductions in hospital LOS. 18 , 19 , 26 , 27 , 28 , 29 , 30 Centers with high rates of ED boarding of patients who are critically ill and those considering implementing an ED‐ICU can consider these findings in the context of their individual practice environments to best mitigate detrimental effects of ED boarding of patients who are critically ill on the local scale. With increasing numbers of ED‐ICUs and more centers considering implementing similar units, continued assessment of outcomes (including prospective research) to guide further development is essential.…”
Section: Discussionmentioning
confidence: 99%
“…Patients transferred for end‐of‐life care were excluded. 19 The sample size was determined by the time interval of data collection: although EC3 opened in February 2015, we included patients from August 1, 2017, forward to allow a “wash out” period given the operational and clinical complexities of implementing an ED‐ICU.…”
Section: Methodsmentioning
confidence: 99%
“…More broadly, as focus is shifting from proving the benefit of LPV to proving it can be implemented and adhered to, an ED-ICU is one strategy to increase LPV adherence (39). Additionally, these findings add to the robust patient and resource utilization outcomes in other common disease states associated with an ED-ICU (26)(27)(28)(29)(30)(31). Health systems may consider these results when determining the feasibility of ED-ICU implementation and future work should examine outcomes associated with ED-ICUs at other institutions.…”
Section: Discussionmentioning
confidence: 99%
“…To combat this and to optimize early delivery of high-quality critical care, ED-based ICUs (also known as Resuscitative Care Units) have been implemented at a small number of institutions across the United States (25). In other disease processes, an ED-ICU has been associated with improved outcomes, including decreased mortality, inpatient ICU admission, and resource utilization (15,(26)(27)(28)(29)(30)(31). There are no prior investigations on the impact of an ED-ICU on adherence to LPV for ED patients receiving mechanical ventilation.…”
mentioning
confidence: 99%